Association between Increased Gastric Juice Acidity and Sliding Hiatal Hernia Development in Humans. - Hiroshi Kishikawa; Kayoko Kimura; Asako Ito; Kyoko Arahata; Sakiko Takarabe; Shogo Kaida; Takanori Kanai; Soichiro Miura; Jiro Nishida (PLoS ONE, 2017)
Several clinical factors; overweight, male gender and increasing age, have been implicated as the etiology of hiatal hernia. Esophageal shortening due to acid perfusion in the lower esophagus has been suggested as the etiological mechanism. However, little is known about the correlation between gastric acidity and sliding hiatus hernia formation. This study examined whether increased gastric acid secretion is associated with an endoscopic diagnosis of hiatal hernia.A total of 286 consecutive asymptomatic patients (64 were diagnosed as having a hiatal hernia) who underwent upper gastrointestinal endoscopy were studied. Clinical findings including fasting gastric juice pH as an indicator of acid secretion, age, sex, body mass index, and Helicobacter pylori infection status determined by both Helicobacter pylori serology and pepsinogen status, were evaluated to identify predictors in subjects with hiatal hernia.Male gender, obesity with a body mass index >25, and fasting gastric juice pH were significantly different between subjects with and without hiatal hernia. The cut-off point of fasting gastric juice pH determined by receiver operating curve analysis was 2.1. Multivariate regression analyses using these variables, and age, which is known to be associated with hiatal hernia, revealed that increased gastric acid secretion with fasting gastric juice pH <2.1 (OR = 2.60, 95% CI: 1.38-4.90) was independently associated with hiatal hernia. Moreover, previously reported risk factors including male gender (OR = 2.32, 95% CI: 1.23-4.35), body mass index >25 (OR = 3.49, 95% CI: 1.77-6.91) and age >65 years (OR = 1.86, 95% CI: 1.00-3.45), were also significantly associated with hiatal hernia.This study suggests that increased gastric acid secretion independently induces the development of hiatal hernia in humans. These results are in accordance with the previously reported hypothesis that high gastric acid itself induces hiatal hernia development.